"Brush model" for the analysis of flat belt transmissions in steady-state conditions. (January 2020) - Frendo, F.; Bucchi, F.
Abstract: In the present work a novel mathematical model for the analysis of the contact actions between belt and pulleys, particularly suited for flat reinforced rubber belt, is presented. The model considers the tension member, composed of the reinforcement fibers, inextensible, and the rubber matrix, which is subjected to tangential stress, as a continuum bed of elastically deformable bristles, fixed to the tension member on one side and in contact with the pulley on the other side. The deformation of the matrix is inversely proportional to the bending stiffness of the bristles, while friction conditions determine the local adhesion/sliding behavior between belt and pulleys. The proposed model can give a detailed description of the contact conditions along the whole contact arc and is able to describe the stick–slip phenomenon which has been experimentally observed by some authors. The model assesses also the power losses due to the contact stresses and to the elastic deformation of the matrix. The results of the model are discussed in comparison with results from classical models, Grashof and Firbank models, available in the technical literature.